Does Mobile Phone Tele-Reminder Increased Iron Status and Diet Quality of Pregnant Women Availing Antenatal Care Services at Phebe and Charles B. Dunbar Hospitals Bong County, Liberia A Cluster Randomized Control Trial (American Journal of Medical Science and Innovation, 2023)
Anemia in pregnancy is a serious public health problem in Liberia. This study aimed to assess the effect of mobile phone tele-reminder on the iron status and diet quality of pregnant women in Liberia. A two-arm, double-blinded cluster randomized control trial was conducted in this study, with ANC screening rooms as a unit of randomization. At the Phebe and Charles B. Dunbar hospitals in Bong County, Liberia, 150 pregnant women who had never previously attended an ANC were recruited for the study (75 intervention women and 75 control women). Iron status measured as hemoglobin (g/dl) and diet quality were primary outcomes of this study. Secondary outcome measures were adherence to daily iron and folic acid supplementation and prevalence of anemia among pregnant women with malaria infection. The analysis was an intent-to-treat. The effect of the intervention on the primary study outcome (iron status) was examined using an independent sample t-test (for group-level analysis). Effects of treatment on diet quality was measured using the Fisher’s Exact Test. A binary logistic regression with a 95% Confidence Interval (CI) was used to analyze the effect of treatment on secondary outcomes. Pregnant women assigned to the intervention group had a significantly greater mean hemoglobin level after the two interventions, t (2.4) = 447, p